Study on clinical, laboratory features and the result of minimal residual disease after induction phase in childhood acute lymphoblastic leukemia at Hue Central Hospital in Vietnam - Hoa, Nguyen Thi Kim; Viet, Phan Hung; Hao, Tran Kiem; Son, Bui Binh Bao; Thanh, Bui Thi Thu; Hoa, Phan Thi Thuy; Ha, Chau Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Acute lymphoblastic leukemia (ALL) is the most common malignant disease in children. Mininal residual disease (MRD) levels after induction phase predict outcome and may select patients for therapy intensification. Objective: To analyse clinical presentations, laboratory features, especially the result of minimal levels in childhood acute lymphoblastic leukemia patients Methods: It was a prospective study on chilhood acute lymphoblastic leukemia patients who admitted hospital since April, 2018 to May, 2020. Results: There were 38 new patients, in which, 68.4% patients with standard risk, and 31.6% patients with high risk; the ratio of male to female was 2.16:1. The median age was 4.0 years (range: 0.66 to 15). The percentage of B-ALL, T-ALL and combined B and T- ALL were 81.6%, 15.8% and 2.6% respectively. The most common symptoms were anemia (86.8%), fever (76.3%), hepatomegaly (68.4%), splenomegaly (60.5%), enlarged lymph nodes (55.3%). For laboratory features, 26.4% patients had white blood cell (WBC) ≥ 50x109/l, 76.3% patients had platelet (PLT) < 100x109/l, 84.6% patients had blood hemoglobin level (Hb) < 10 g/dl. Lactate dehydrogenase (LDH) and C- reative protein (CRP) increased in most of patients, accounted for 89.5% and 73.7% respectively. After induction, complete remission which based on less than 5% blasts achieved 97.4%. However, MRD after induction phase with threshold ≤ 0.01% accounted for 78.9%. And based on MRD, we adjusted intensive chemotherapy for 4 patients. Conclusion: The most common clinical presentation was anemia, fever, hepatosplenomegaly, bone pain, bleeding. The result of MRD levels is more sensitive and precise to evaluate the responde after induction phase. Therefore, we could adjust intensitive therapy for some patients with high MRD levels to improve the treatment outcome.